Determining Equine Influenza Virus Vaccine Efficacy—The Specific Contribution of Strain Versus Other Vaccine Attributes - Sylvia Reemers; Denny Sonnemans; Linda Horspool; Sander van Bommel; Qi Cao; Saskia van de Zande (Vaccines, 2020)
Vaccination is an effective tool to limit equine influenza virus (EIV H3N8) infection, a contagious respiratory disease with potentially huge economic impact. The study assessed the effects of antigenic change on vaccine efficacy and the need for strain update. Horses were vaccinated (V1 and V2) with an ISCOMatrix-adjuvanted, whole inactivated virus vaccine (Equilis Prequenza, group 2, FC1 and European strains) or a carbomer-adjuvanted, modified vector vaccine (ProteqFlu, group 3, FC1 and FC2 HA genes). Serology (SRH, HI, VN), clinical signs and viral shedding were assessed in comparison to unvaccinated control horses. The hypothesis was that group 2 (no FC2 vaccine strain) would be less well protected than group 3 following experimental infection with a recent FC2 field strain (A/equi-2/Wexford/14) 4.5 months after vaccination. All vaccinated horses had antibody titres to FC1 and FC2. After challenge, serology increased more markedly in group 3 than in group 2. Vaccinated horses had significantly lower total clinical scores and viral shedding. Unexpectedly, viral RNA shedding was significantly lower in group 2 than in group 3. Vaccination induced protective antibody titres to FC1 and FC2 and reduced clinical signs and viral shedding. The two tested vaccines provided equivalent protection against a recent FC2 EIV field strain.